2019
DOI: 10.1055/s-0039-1683379
|View full text |Cite
|
Sign up to set email alerts
|

Frontotemporal Dementia: A Clinical Review

Abstract: Frontotemporal dementias are a clinically, neuroanatomically, and pathologically diverse group of diseases that collectively constitute an important cause of young-onset dementia. Clinically, frontotemporal dementias characteristically strike capacities that define us as individuals, presenting broadly as disorders of social behavior or language. Neurobiologically, these diseases can be regarded as “molecular nexopathies,” a paradigm for selective targeting and destruction of brain networks by pathogenic prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 103 publications
(128 reference statements)
0
38
0
3
Order By: Relevance
“…One important biological rationale for assessing phobic reactivity in dementia syndromes is the neuroanatomy of phobic responses: available evidence in the healthy brain has implicated a distributed network of brain regions in the generation of specific phobic responses, including amygdala, insula, medial prefrontal and extrastriate visual cortices ( Caseras et al., 2010 ; Del Casale et al., 2012 ; Ipser, Singh, & Stein, 2013 ; Linares et al., 2014 , 2012 ; Mobbs et al., 2010 ; Stefanescu, Endres, Hilbert, Wittchen, & Lueken, 2018 ; Wabnegger, Scharmüller, & Schienle, 2014 ). These areas closely overlap the core brain networks targeted in canonical syndromes of FTD and AD ( Mahoney et al., 2015 ; Marshall et al., 2019 ; Raj, Kuceyeski, & Weiner, 2012 ; Seeley, Crawford, Zhou, Miller, & Greicius, 2009 ; Sivasathiaseelan et al., 2019 ; Warren et al., 2013 ; Warren, Fletcher, & Golden, 2012 ; Zhou, Gennatas, Kramer, Miller, & Seeley, 2012 ), suggesting that studying phobic responses in dementias may illuminate our understanding of the neural mechanisms critical for mediating phobic reactivity in health as well as neurodegenerative disease.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…One important biological rationale for assessing phobic reactivity in dementia syndromes is the neuroanatomy of phobic responses: available evidence in the healthy brain has implicated a distributed network of brain regions in the generation of specific phobic responses, including amygdala, insula, medial prefrontal and extrastriate visual cortices ( Caseras et al., 2010 ; Del Casale et al., 2012 ; Ipser, Singh, & Stein, 2013 ; Linares et al., 2014 , 2012 ; Mobbs et al., 2010 ; Stefanescu, Endres, Hilbert, Wittchen, & Lueken, 2018 ; Wabnegger, Scharmüller, & Schienle, 2014 ). These areas closely overlap the core brain networks targeted in canonical syndromes of FTD and AD ( Mahoney et al., 2015 ; Marshall et al., 2019 ; Raj, Kuceyeski, & Weiner, 2012 ; Seeley, Crawford, Zhou, Miller, & Greicius, 2009 ; Sivasathiaseelan et al., 2019 ; Warren et al., 2013 ; Warren, Fletcher, & Golden, 2012 ; Zhou, Gennatas, Kramer, Miller, & Seeley, 2012 ), suggesting that studying phobic responses in dementias may illuminate our understanding of the neural mechanisms critical for mediating phobic reactivity in health as well as neurodegenerative disease.…”
Section: Introductionmentioning
confidence: 95%
“…This is a fortunate state of affairs but also makes the experience of fear difficult to study experimentally. It presents a particularly pertinent challenge in neurodegenerative diseases, notably the frontotemporal dementias (FTD), in which altered emotion processing is a leading clinical issue and potentially a core pathophysiological principle ( Kumfor & Piguet, 2012 ; Lyketsos et al., 2000 ; Marshall et al., 2019 ; Rascovsky et al., 2011 ; Sivasathiaseelan et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over longer timescales, difficulties with prospection and retrospection have been documented in bvFTD and SD (49,(52)(53)(54)(55)(56). There are currently no validated instruments to assess clockwatching and more general inflexibility or obsessionality around time, although these are frequently associated with both bvFTD and SD (31,57,58). Impaired awareness of time and associated disruptions of socio-emotional behaviors in these diseases potentially take a substantial toll on patient well-being and care burden and therefore constitute a significant clinical issue.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the heterogeneity of FTLD, a precise description of the associated movement disorders may help to better establish the antemortem diagnosis in these patients, which is challenging even for experienced clinicians. 9 This is of particular importance given the future development of potential disease-modifying drugs targeting specific protein aggregates. [10][11][12] The aim of this study is to provide a detailed characterization of the movement disorders in a large group of patients with a postmortem confirmed diagnosis of FTLD and establish potential clinicopathologic associations between movement disorders and neuropathological findings.…”
mentioning
confidence: 99%
“…Previous efforts have been made to describe the parkinsonian features of these conditions although studies have been limited to genetically confirmed patients (excluding a large proportion of patients), single case reports, or small series, 7,8 and a systematic phenomenological characterization of the movement disorders associated with pathology‐confirmed FTLD is lacking. Because of the heterogeneity of FTLD, a precise description of the associated movement disorders may help to better establish the antemortem diagnosis in these patients, which is challenging even for experienced clinicians 9 . This is of particular importance given the future development of potential disease‐modifying drugs targeting specific protein aggregates 10‐12 .…”
mentioning
confidence: 99%